Elf - Favreau, Jon; Ferrell, Will, 1967-; Caan, James; Newhart, Bob (Burbank, CA : Warner Home Video, 2004)
A human child raised by elves at the North Pole, learns of his human family and goes to live with them in New York City.
Originally released as a motion picture in 2003.
Features: deleted scenes, Tag along with Will Ferrell, Film school for kids, That's a wrap..., Lights, cameras, puffins!, How they made the North Pole, Deck the halls, Christmas in Tinseltown, Santa mania, Kids on Christmas, audio commentary with Will Ferrell and Jon Favreau, interactive game, karaoke, read along, DVD-Rom features: screenplay access, make your own Christmas book activity, send personalized greetings.
Will Ferrell, James Caan, Bob Newhart, Edward Asner, Mary Steenburgen.
MPAA rating: PG.
DVDs, Dolby digital stereo.
In English or Spanish.
Keywords: Elves -- Drama; Christmas plays; Video recordings for hard of hearing people; Feature films; Comedy films